Islamic banks’ commitment to Sharia controls (Murabaha contracts, Ijarah contracts) Status (Banks working in Jordan) - Al-Taani, Attallah Hassan Mohamed (International Journal of Membrane Science and Technology, 2023)
This study focused on Islamic banks’ adherence to Sharia controls when executing contracts, and the focus was on the most common debt contracts, which are contracts that all banks (Islamic and conventional banks) compete for. What distinguishes Islamic banks from traditional ones is the commitment to Sharia controls in Islamic banks. The most important results were that the motive for dealing with Islamic banks is religious motive, and that Islamic banks adhere to Sharia controls when drafting contracts, but their employees do not adhere to these controls when executing contracts. Islamic banks focus their investment efforts on debt contracts and on the youth category with fixed incomes, least riskiness, and not to focus on other Islamic contracts (Mudarabah, Musharaka, ...) that are riskier. There is no relationship between the type of contract and the extent of compliance with Sharia controls when executing contracts in Islamic banks.